2019
DOI: 10.3390/molecules24010203
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic Gene Content of the ‘Perfume Lichens’ Evernia prunastri and Pseudevernia furfuracea

Abstract: Lichen-forming fungi produce a vast number of unique natural products with a wide variety of biological activities and human uses. Although lichens have remarkable potential in natural product research and industry, the molecular mechanisms underlying the biosynthesis of lichen metabolites are poorly understood. Here we use genome mining and comparative genomics to assess biosynthetic gene clusters and their putative regulators in the genomes of two lichen-forming fungi, which have substantial commercial value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 106 publications
5
59
1
Order By: Relevance
“…2016 ). Genomic data sets are also increasing our knowledge of the presence and domain architecture of PKSs, which are key for the biosynthesis of fungal phenolics, at an unprecedented rate ( Calchera et al. 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…2016 ). Genomic data sets are also increasing our knowledge of the presence and domain architecture of PKSs, which are key for the biosynthesis of fungal phenolics, at an unprecedented rate ( Calchera et al. 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The biosynthesis potential of C. uncialis and other lichens is still poorly explored due to the lack of any experimental evidence for definite linking biosynthetic gene clusters with secondary metabolites. Only recently, first attempts in the functional genome annotation have been carried out (Bertrand et al, 2018a;Calchera et al, 2019). Nevertheless, their importance as a natural source of polyketides from which a number of pharmacologically active substances is derived (Helfrich et al, 2014), would increase the intensity of ongoing research.…”
Section: Discussionmentioning
confidence: 99%
“…The C. uncialis genome was proposed to include enzymes for grayanic acid, patulin and betaenone biosynthesis, and the latter two were not found in other lichen species (Bertrand et al, 2018b). A recent genome mining study of other lichen species, Evernia prunastri and Pseudevernia furfuracea, reported 80 biosynthetic gene clusters in the first one and 51 in the latter (Calchera et al, 2019) that also included polyketide synthases, non-ribosomal peptide synthetases and terpene synthases.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, gene clusters associated with the biosynthesis of secondary metabolites (e.g. polyketides) were identified in lichenizing fungi (Bertrand et al ., ; Dal Grande et al ., ; Wang et al ., ; Calchera et al ., ), and also for a gene cluster tentatively involved in the biosynthesis of usnic acid in Cladonia uncialis (Abdel‐Hameed et al ., ). This gene cluster encodes a putative nonreducing polyketide synthase named methylphloroacetophenone synthase, and a cytochrome P450 oxidase named methylphloroacetophenone oxidase.…”
Section: Introductionmentioning
confidence: 99%